One-Pot Synthesis of Ag/Quaternary Ammonium Salt Co-Decorated Mesoporous Silica Nanoparticles for Synergistic Treatment of Cancer and Bacterial Infections - Zhang, Hanyuan; Xu, Jianxiang; Zhang, Xu; Wang, Teng; Zhou, Dairan; Shu, Wei; Zhao, Tingting; Fang, Weijun (Frontiers in Bioengineering and Biotechnology, 2022)
Developing drug delivery nanosystems with both anticancer and antibacterial effects is of great clinical value. Herein, we report a facile approach to synthesize Ag and QAS co-decorated mesoporous silica nanoparticles, namely Ag/QAS-MSNs, for synergistic treatment of cancer and bacterial infections. The in vitro studies demonstrated that the Ag/QAS-MSNs not only had a strong antibacterial activity against the bacterial pathogens, but also could efficiently induce cancer cell death through an apoptotic pathway. Moreover, in vivo combination therapy with Ag and QAS in the Ag/QAS-MSNs was also tested in a nude mouse tumor model, and a significant synergistic anticancer effect, that is superior to that obtained by therapy with Ag-MSNs or QAS-MSNs alone, was achieved. Thus, the Ag and QAS co-decorated mesoporous silica nanoparticles have a promising future acting as a potent anticancer agent with high antibacterial performance.